Symbolism in contemporary mosque architecture discourse: an integrative literature review - Fireza, Doni; Sabil, Azmal; Utaberta, Nangkula (SINERGI, 2025)
Contemporary mosque architecture, as part of postmodern architecture, is an interesting focus of discussion, which has dimension of subjective meanings represented or symbolized in the architectural design. Thus, this can be viewed as a medium of communication between architects and the public, or in the context of mosque architecture, as a medium for conveying Islamic teachings to the ummah. To understand how design symbolism communicates ideas in architecture, selected publications on contemporary mosque architecture were reviewed within the postmodern architectural paradigm. This study aims to critically develop new ideas and perspectives from contemporary mosque architecture as a communication medium of religious values and teachings. Using integrative literature review as methodology, the result is the construction of new ideas and perspectives regarding the relationship among aspects in the paradigm of postmodernism developed in mosque architectural history.